A perspectiva dos cuidados paliativos e a questão do morrer no contemporâneo - Silva, Denise de Souza (2015)
Death is the most individualizador and at the same time more egalitarian in human existence. The problem is not death, but the fact that the subject dies. This work-paper is proposed to study the experience from the perspective of palliative care, in order to understand how the subject experience death and dying. It was carried out an incursion in a ethnographic palliative care service, allowing on-the-spot experience of dealing daily with the approaching death and the discussion about death and dying from the subject (professionals, patients and family members) and their singularities in this particular wait time-not without before, resume a historical perspective of this theme. Each season there is a way to go and a look into the death. The speech of the palliative care produces a way to die that meets the demands of that time, although it is an attempt to escape the neoliberal, rationality is the model of the scientific thinking and the tecnociências that allows your emergency. As a care model inserted in the biomedical field has a general version of how to deal with the illness or death, however the study showed that when the subject is confronted with the critical facts of life emerges your uniqueness.